Support Needs and Service Provision for Social Participation of Persons with Intellectual Disabilities - Maebara, Kazuaki; Yaeda, Jun; Imai, Aya; Yamada, Yukiya (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Person-centered support based on self-determination is needed for persons with intellectual disabilities to participate in society in Japan. However, work supporters may be unable to provide sufficient support for this purpose. Objective: This study analyzes work supporters’ implementation of necessary support to understand persons with intellectual disabilities’ support needs. Methods: This study compared persons with intellectual disabilities’ support needs with the implementation of support from work supporters at vocational rehabilitation agencies (Survey 1) and the support needs of persons with intellectual disabilities (Survey 2). Results: The results showed that the persons with intellectual disabilities most required support related to daily living. This was consistent with the support provided by the work supporters. However, there were situations wherein the smooth transition of support was not provided, which was attributed to the lack of knowledge and cross-disciplinary involvement of the work supporters in the employment-related welfare services for persons with disabilities. Conclusions: Possessing the knowledge and skills required for vocational rehabilitation and working in vocational rehabilitation agencies could contribute to the smooth transition of support for persons with intellectual disabilities. Accordingly, the results can clarify the required role of work supporters for persons with intellectual disabilities future participation in society.